Integration of Multicultural Discovery Learning and Computational Thinking in Elementary Mathematics Education: A Systematic Literature Review - Hendri, Sherlyane; Sa’dijah, Cholis; Muksar, Makbul (Journal of Ecohumanism, 2025)
As elementary mathematics education evolves to meet the demands of a culturally diverse, technologically advanced world, this systematic review examines the integration of discovery learning, multicultural education, and computational thinking, addressing a significant gap in current research. Following PRISMA guidelines, we analyzed 32 high-quality studies (2020-2024) selected from an initial pool of 4,230 articles across Scopus and ERIC databases, focusing on implementation strategies, student outcomes, and integration barriers. Our findings reveal that successful implementation of discovery learning in multicultural, computationally-driven classrooms requires careful scaffolding and cultural adaptation, with 78% of studies emphasizing the crucial role of teacher preparedness. The combination of computational thinking with culturally relevant teaching enhanced student engagement and mathematical understanding, particularly in problem-solving tasks (65% of studies), while significant barriers included inadequate teacher training (82%), limited culturally relevant resources (71%). These results highlight the urgent need for enhanced teacher professional development, culturally responsive computational thinking resources, and flexible implementation frameworks that accommodate diverse learning styles while maintaining the benefits of discovery learning, ultimately contributing to developing more inclusive and effective elementary mathematics education practices.